A study of the Effects of Physiotherapy on Knee Osteoarthritis (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Osteoarthritis (OA) of the knee is a common chronic illness that causes pain and limited movement, greatly reducing quality of life. To manage knee OA, this randomised controlled trial evaluated the effectiveness of a comprehensive physiotherapy program that included exercise treatment, manual therapy, and patient education. One hundred individuals with moderate to severe osteoarthritis (OA) were randomised to be in one of two groups: the intervention group or the control group, which received conventional care. Supervised exercises, manual joint mobilisations, soft tissue manipulations, and education sessions on disease management and lifestyle adjustments were all part of the 12-week intervention. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to measure pain and physical function as primary objectives. The Short Form-36 (SF-36) health survey was used to measure knee range of motion, muscle strength, and quality of life as secondary goals. The intervention group significantly outperformed the control group in terms of knee range of motion, muscle strength, and WOMAC pain and function scores (p < 0.001), according to the results. Furthermore, the intervention group's quality of life scores in the domains of pain and physical functioning were significantly higher. These results, which are in line with other research emphasizing the importance of exercise, manual treatment, and patient education in improving clinical outcomes, demonstrate the many advantages of a physiotherapy program in the effective management of knee OA. This study supports the integration of comprehensive physiotherapy into standard knee OA treatment protocols to improve patient well-being and functional capabilities. Future research should focus on optimizing these interventions for broader clinical application.